BEBERAPA CATATAN KRITIS GAGASAN PERUBAHAN TERBATAS UUD 1945: MENUJU NEGARA HUKUM YANG BERMARTABAT - Abdul Mukhtie Fadjar (Legal Spirit, 2017)
One of the agenda of the Reform in Indonesia in 1998 was Constitution Reform resulting in Amendment of Constitution of the Republic of Indonesia Year 1945 (abbreviated 1945 Constitution 1945) four times. In the present era, the idea of limited change of the 1945 Constitution is being widely discoursed to encourage the establishment of a dignified State of Law in accordance with the basic philosophy of the Pancasila state. However, learning from the experiences in the process of amending the 1945 Constitution four times gradually (1999, 2000, 2001, and 2002), realizing the idea of a Dignified Law Country does not necessarily have to go through Constitutional Amendments. Rather it can be done through the interpretation of the constitution, either by the legislature, the executive, or by the judiciary, provided that in the interpretation of the constitution, the institutions are able to capture the moral message of Pancasila and the 1945 Constitution of the Republic of Indonesia. Keywords: Limited Changes, 1945 Constitution, Dignified Law Country.